Prospective study of cytotoxic T lymphocyte responses to influenza and antibodies to human T lymphotropic virus-III in homosexual men. Selective loss of an influenza-specific, human leukocyte antigen-restricted cytotoxic T lymphocyte response in human T lymphotropic virus-III positive individuals with symptoms of acquired immunodeficiency syndrome and in a patient with acquired immunodeficiency syndrome. - Shearer, G M (1985)
Peripheral blood leukocytes (PBL) from 18 homosexual men who did not have acquired immunodeficiency syndrome (AIDS) and from 9 heterosexual men were repetitively tested for their ability to generate HLA self-restricted cytotoxic T lymphocyte responses to influenza virus (flu-self) over a 2-yr period. The sera of the same donors were tested for antibodies to human T lymphotropic virus-III (HTLV-III). Six of the homosexual and none of the heterosexual donors consistently generated weak cytotoxic T lymphocyte responses to flu-self. Seven of the homosexual and none of the heterosexual donors were seropositive for antibodies to HTLV-III. No obvious correlation was detected between weak flu-self cytotoxic T lymphocyte responses and antibodies to HTLV-III. However, one homosexual donor generated no detectable cytotoxic T lymphocyte activity to flu-self, although he was a strong responder to HLA-alloantigens. This donor had an OKT4:OKT8 ratio of 0.4 and was seropositive for HTLV-III antigens; HTLV-III virus was identified in his PBL; and he developed AIDS during the course of this study. A second donor with lymphadenopathy and who was seropositive for HTLV-III antigens exhibited marginal cytotoxic T lymphocyte activity to flu-self which he subsequently lost. PBL from two patients, one with Kaposi's sarcoma and one with generalized lymphadenopathy, were also tested for cytotoxic T lymphocyte responses to flu-self and to alloantigens. Both donors failed to generate cytotoxic T lymphocyte to flu-self, but generated strong cytotoxic T lymphocyte responses to alloantigens. The selective loss of an HLA-restricted cytotoxic T lymphocyte response without loss of HLA alloantigenic cytotoxic T lymphocyte activity may be an important functional immunologic characteristic in the development of AIDS.